2014
DOI: 10.1111/ene.12400
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal atrial fibrillation occurs often in cryptogenic ischaemic stroke. Final results from the SURPRISE study

Abstract: One in five patients with CS had PAF, which occurred at low burden and long after stroke. Future studies should determine the role of implantable cardiac monitors after stroke and determine the potential therapeutic benefit of OAC treatment of patients with PAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 27 publications
0
88
0
4
Order By: Relevance
“…They offer greatly extended monitoring periods and high detection rates. 26 For the majority of patients, however, our trial suggests that a relatively brief duration of noninvasive monitoring may be sufficient for routine application, with 88% of sustained PAF identified within 72 hours. Excellent reporting agreement between treating stroke physicians and the electrocardiology laboratory facilitates immediacy of clinical decisions and could limit costs.…”
Section: Strokementioning
confidence: 81%
See 1 more Smart Citation
“…They offer greatly extended monitoring periods and high detection rates. 26 For the majority of patients, however, our trial suggests that a relatively brief duration of noninvasive monitoring may be sufficient for routine application, with 88% of sustained PAF identified within 72 hours. Excellent reporting agreement between treating stroke physicians and the electrocardiology laboratory facilitates immediacy of clinical decisions and could limit costs.…”
Section: Strokementioning
confidence: 81%
“…12 The AM compared very favorably against rates reported for 24-hour Holter monitoring 12 or repeated 12-lead ECGs 24 and achieved similar detection rates to extended-duration Holter monitoring, 23 automated software-assisted continuous electrophysiological monitoring, 25 and implantable cardiac-event recorders. 26 Thus, guideline-based practice underdetects AF. In contrast, we detected sustained PAF episodes that justify anticoagulation in an additional 16% of patients, within 14 days.…”
Section: Strokementioning
confidence: 99%
“…16,17 Long-term continuous monitoring using insertable cardiac monitors (ICMs) has been shown to be the most comprehensive method of detecting paroxysmal and asymptomatic AF in CS patients. 10,[19][20][21][22] The incidence of AF detected by ICMs in this population ranges from 16% to 33.7%, depending on the episode duration definition, the length of monitoring, and patient selection. 6 OAC therapy is highly effective in reducing recurrent stroke in patients with AF.…”
Section: Long-term Monitoring Of Atrial Fibrillationmentioning
confidence: 99%
“…However, numerous small, singlecenter studies have demonstrated that significant proportions of patients with strokes initially believed to be cryptogenic actually have episodes of occult AF detected beyond 30 days of monitoring via even more extensive rhythm surveillance with insertable cardiac monitors (ICMs) [13][14][15][16][17] .…”
mentioning
confidence: 99%